The Role of Transformational Leadership in the Successful Implementation of Information Systems in the Government Sector - Faradina, Ryan; Mabrur, Azas (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This study examines the mediating role of transformational leadership in the successful implementation of information systems in government. Unlike previous research conducted in the commercial sector, the implementation of information systems in the government sector is mandatory so operational variables need to be modified. The data used are primary data collected from 86 respondents who are information system operators. Analysis was performed using Partial Least Square (PLS) SEM. The results of the study show that system quality, information quality, and service quality have a positive effect on the successful implementation of information systems in government. These results also prove that transformational leadership mediates the relationship between overall quality and information system usage. This supports the hypothesis regarding the importance of transformational leadership in the successful implementation of information systems.